Prediction Method for the Radial Runout of Inner Ring in Cylindrical Roller Bearings. (31st May 2017) - Yu, Yongjian; Chen, Guoding; Li, Jishun; Xue, Yujun; Pang, Bitao
Abstract : The motion error of assembled bearing depends on the geometric profile of bearing components. Therefore, it is crucial to establish the relationship between geometric error of bearing components and motion error of assembled bearing, which contributes to improving the rotational accuracy of assembled bearing in the design and machining of the bearing. The main purpose of this research is to propose an accurate method for predicting the radial runout of inner ring based on the geometrical constraint model of cylindrical roller bearings. In the geometrical constraint model, dimension and form errors in the inner raceway, the outer raceway, and rollers are considered, and the change of contact positions between the raceways and rollers caused by geometric errors of bearing components is taken into account. This method could predict the radial runout of inner ring after bearing components with geometric error are assembled. In order to testify the validity of the proposed prediction method, two particular cases in which the profiles of the inner raceway are circle and ellipse are selected, and the analysis algorithms for the radial runout of inner ring are derived. Two analytical results obtained from the analysis algorithms validate accuracy and effectiveness of the proposed prediction method.